Medical signal and imaging analysis for diagnosis of coronary artery disease - Muhammad Khairil Azhar Ridzwan (2019)
Coronary Artery Disease (CAD), also known as Ischemic Heart Disease (IHD) is one of the most common heart diseases. In Singapore, CAD is the most common cause of death among other cardiovascular disease and accounts for the third highest number of deaths [1]. CAD occurs when the artery narrows due to the build-up of cholesterol plaque on the wall of the vessel thus limiting blood flow to the heart. When the artery narrows severely, symptoms such as chest pain or shortness of breath may occur. Thus, early detection of the disease is crucial in mitigating the escalation of the disease which might lead to death. This Final Year Project studies medical signals and images for diagnosis of CAD. There are two sections to this project. First section comprises of the analysis of medical images procured from tests conducted on swine artery using ImageJ, an image processing software. The final section consists of simulation of collagen fibres with the aid of Lumerical FDTD Solutions, a software for modelling nanophotonic devices, processes and materials.